Comparison of the Separation Characteristics of Polyvinyl Alcohol Membrane in Dehydration of Benzene and Toluene Using Pervaporation - Ghasem Khatinzadeh; Ahmad Roozbaheni; Ali Mehdizdaeh (Journal of Petroleum Science and Technology, 2018)
Pervaporation (PV) is a well-established membrane technique used in separation; especially dehydration of organic solvents. Along with other parameters such as permeate pressure and feed temperature; feed composition is an important parameter, which affects separation characteristics and membrane performance in pervaporation. In this paper, the separation characteristics of a hydrophilic polyvinyl alcohol (PVA) membrane in the dehydration of benzene and toluene by pervaporation in the temperature range of 30-60 °C and permeate pressure of 7 mmHg have been compared. The results show that the difference in the molecular sizes of benzene and toluene and their mutual solubilities with water cause differences in separation parameters, so that for example at 50 °C, in dehydration of benzene water flux and water concentration in the permeate are 0.53 (g/hm2) and 2.03 (wt.%) respectively, while the corresponding values in toluene dehydration are 0.61 (g/hm2) and 3.19 (wt.%) respectively. Therefore these amounts result in higher pervaporation separation index (PSI) for toluene compared to benzene.